The global research of magnetic resonance imaging in Alzheimer’s disease: a bibliometric analysis from 2004 to 2023 - Xiaoyu Sun; Xiaoyu Sun; Jianghua Zhu; Jianghua Zhu; Ruowei Li; Ruowei Li; Yun Peng; Yun Peng; Lianggeng Gong; Lianggeng Gong (Frontiers in Neurology)
BackgroundAlzheimer’s disease (AD) is a common neurodegenerative disorder worldwide and the using of magnetic resonance imaging (MRI) in the management of AD is increasing. The present study aims to summarize MRI in AD researches via bibliometric analysis and predict future research hotspots.MethodsWe searched for records related to MRI studies in AD patients from 2004 to 2023 in the Web of Science Core Collection (WoSCC) database. CiteSpace was applied to analyze institutions, references and keywords. VOSviewer was used for the analysis of countries, authors and journals.ResultsA total of 13,659 articles were obtained in this study. The number of published articles showed overall exponential growth from 2004 to 2023. The top country and institution were the United States and the University of California System, accounting for 40.30% and 9.88% of the total studies, respectively. Jack CR from the United States was the most productive author. The most productive journal was the Journal of Alzheimers Disease. Keyword burst analysis revealed that “machine learning” and “deep learning” were the keywords that frequently appeared in the past 6 years. Timeline views of the references revealed that “#0 tau pathology” and “#1 deep learning” are currently the latest research focuses.ConclusionThis study provides an in-depth overview of publications on MRI studies in AD. The United States is the leading country in this field with a concentration of highly productive researchers and high-level institutions. The current research hotspot is deep learning, which is being applied to develop noninvasive diagnosis and safer treatment of AD.